Synthesis of zeolites from low-cost feeds and its sustainable environmental applications. Issue 1 (February 2023) - Gao, Shuai; Peng, Hong; Song, Bing; Zhang, Jinxuan; Wu, Weixi; Vaughan, James; Zardo, Peter; Vogrin, John; Tulloch, Sylvia; Zhu, Zhonghua
Abstract: Zeolites are one of the most widely used adsorbents, versatile for multiple purposes including the emerging areas of carbon capture and wastewater treatment. However, the scaling up of zeolite-based adsorption is challenged mainly by the high cost required for its synthesis. Successfully producing high-performance zeolite adsorbents from low-value or even waste raw materials such as mineral, industrial and agricultural wastes is alluring in that it will (i) reduce the costs for zeolite preparation and high-value applications and (ii) provide a value-adding means for managing various wastes. This review is thus prepared to (1) overview the state-of-art zeolite synthesis methods using low-value resources or waste streams and their corresponding methods, (2) understand the performances of various low-value ends derived zeolites for gas adsorption with a focus on their CO2 capturing capabilities compared to commercial synthetic zeolites, (3) assess the capabilities of these zeolites for wastewater treatment applications compared to commercial synthetic zeolites, and (4) provide perspectives for future studies. The conversion of low-cost feedstock or even wastes is plausible to produce valuable zeolites with performances comparable to commercial synthetic zeolites, calling for progress in developing greener routes for zeolite preparation, addressing the inconsistency of raw materials, and techno-economic assessments based on large-scale preparation and applications. Graphical Abstract: ga1 Highlights: The state-of-art zeolite synthesis methods using low-cost resources were reviewed. The carbon capture performance of low-cost ends derived zeolites was evaluated. The wastewater treatment capacity of synthetic and natural zeolites was assessed. Green routes and inconsistency of raw materials in applications were highlighted.